Causes and features of long-term variability of the ice extent in the Barents Sea - S. B. Krasheninnikova; M. A. Krasheninnikova (Лëд и снег, 2019)
Based on the spectral analysis of a number of estimates of the ice extent of the Barents Sea, obtained from instrumental observational data for 1900–2014, and for the selected CMIP5 project models (MPI-ESM-LR, MPI-ESMMR and GFDL-CM3) for 1900–2005, a typical period of ~60‑year inter-annual variability associated with the Atlantic multidecadal oscillation (AMO) in conditions of a general significant decrease in the ice extent of the Barents Sea, which, according to observations and model calculations, was 20 and 15%, respectively, which confirms global warming. The maximum contribution to the total dispersion of temperature, ice cover of the Barents Sea, AMO, introduces variability with periods of more than 20 years and trends that are 47, 20, 51% and 33, 57, 30%, respectively. On the basis of the cross correlation analysis,  significant links have been established between the ice extent of the Barents Sea, AMO, and North Atlantic Oscillation (NAO) for the  period 1900–2014. A significant negative connection (R = −0.8) of ice cover and Atlantic multi-decadal oscillations was revealed at periods of more than 20 years with a shift of 1–2 years; NAO and ice cover (R = −0.6) with a shift of 1–2 years for periods of 10–20 years; AMO and NAO (R = −0.4 ÷ −0.5) with a 3‑year shift with AMO leading at 3–4, 6–8 and more than 20 years. The periods of the ice cover growth are specified: 1950–1980 and the reduction of the ice cover: the 1920–1950 and the 1980–2010 in the Barents Sea. Intensification of the transfer of warm waters from the North Atlantic to the Arctic basin, under the atmospheric influence caused by the NAO, accompanied by the growth of AMO leads to an increase in temperature, salinity and a decrease of ice cover in the Barents Sea. During periods of ice cover growth, opposite tendencies appear. The decrease in the ice cover area of the entire Northern Hemisphere by 1.5 × 106 km2 since the mid-1980s. to the beginning of the 2010, identified in the present work on NOAA satellite data, confirms the results obtained on the change in ice extent in the Barents Sea.